(untitled) (Scientific journal of the Fergana State University, 2024)
The first acetylene alcohols containing a heteroatom in the molecule - 1-(thiophen-2-yl)prop-2-yn-1-ol, 1-(3 methylthiophen-2-yl)propyn-2-ol-1, 1(furanyl-2)propyn-2- ol-1, 1-(pyridinyl-3)propin-2-ol-1, 1-(quinolinyl-2)propin-2-ol-1, 1-(3-bromopyridinyl-4)propin-2-ol-1 in a benzene solution in the presence of a concentrated catalyst H2SO4 in the esterification reaction with benzoic acid, the process of synthesis of esters- 1-(thiophenyl-2)propynyl benzoate, 1-(3 methylthiophenyl-2)propynyl-2 benzoate, 1-(furanyl-2)propynyl-2 benzoate, 1-(pyridinyl-3)propynyl-2 benzoate, 1-( quinolinyl-2)propynyl-2 benzoate, 1-(3-bromopyridinyl-4)propynyl-2 was carried out. A number of factors influencing the yield of the product have been studied - temperature, reaction duration, influence of the amount of catalyst and solvents, substrate and reagents. Based on the results obtained, the most optimal conditions for the processes were found. The composition, purity, structure and quantum chemical properties of the synthesized esters were confirmed by modern physicochemical methods- IR, 1H-NMR, 13C-NMR spectroscopy, mass spectrometry, chromatography. The efficiency range of the synthesized esters has been determined. Biological properties have been studied.